Polymer and preparation method thereof, retarder and oil well cement paste

By developing a polymer containing hydrophilic main chain and multi-branched chain capping structure as a retarder, the problems of ultra-retarded and long-term non-solidified cement slurry in the long-sealed cement section of the deep well ultra-deep well were solved, and the effect of accelerating the development of cement slurry strength and improving cement quality was achieved.

CN119708346AActive Publication Date: 2025-03-28CHINA NAT PETROLEUM CORP +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311278907.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

In the cementing wells of the long sealing section of the deep well ultra-deep well, the cement slurry of the oil well is prone to excessively slow or long-term non-solidification, resulting in a decrease in cementing quality and an extension of the well construction period.

Method used

A polymer was developed that contains a hydrophilic backbone and a multi-branched chain capping structure with excellent water solubility and ionic complexing capabilities, and is used as a retarder in oil well cement slurry. This polymer has strong retarding ability at high temperatures, and as the temperature decreases, the retarding ability weakens, making it suitable for the construction needs of long-sealing section cementing.

Benefits of technology

By using this polymer as a retarder, the strength development of the oil well cement slurry can be significantly accelerated, ensuring that the compressive strength of the top cement slurry reaches more than 7MPa at 80°C for 48 hours, solving the problems of super-retarding and long-term non-solidification, and not affecting the water loss of the cement slurry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708346A_ABST
    Figure CN119708346A_ABST
Patent Text Reader

Abstract

The invention relates to the field of petroleum drilling auxiliaries, in particular to a polymer and a preparation method thereof, a retarder and oil well cement paste. The polymer comprises a hydrophilic main chain and end-capping structures at the two ends of the hydrophilic main chain, wherein the hydrophilic main chain contains a structural unit A, a structural unit B and a structural unit C; the molar ratio of the structural unit A to the structural unit B to the structural unit C is 10: (0.5-8): (0.1-4); a polymer chain segment in the end-capping structure contains a structural unit D and a structural unit E, and the molar ratio of the structural unit D to the structural unit E is 1: (0.5-5). The polymer serving as a retarder component is applied to long-sealing-section well cementation, the strength development of top cement paste can be accelerated on the premise that the retarding effect of oil well cement paste is guaranteed, the polymer has small influence on the water loss of the oil well cement paste, cement paste formula design and construction safety are facilitated, and the well building cost is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of oil drilling additives, and in particular to a polymer and a preparation method thereof, a retarder and oil well cement slurry. Background Art

[0002] Cementing engineering is to pump oil well cement slurry into the annulus between the casing and the formation according to the design requirements, and after solidification, it can isolate the interlayer fluid in the well, support and protect the casing. The quality of cementing directly affects the oil and gas production capacity of the reservoir and the life of the oil and gas wells. With the depletion of shallow oil and gas resources, the exploration target has turned to deep and ultra-deep layers. Due to the more complex geological structure of deep and ultra-deep wells, the number of casing layers has increased, and the cost of well construction has increased. In order to develop deep oil and gas resources more efficiently and at a low cost, the method of reducing the casing layer design is usually adopted, but this method will inevitably lead to an increase in the one-time sealing length. The thickening time index of oil well cement slurry In order to achieve the construction pumping time required by the cementing design, a certain amount of oil well cement retarder needs to be added to ensure that the oil well cement maintains good fluidity before displacement. Generally speaking, within the applicable temperature range of the retarder, if the same thickening time is achieved, the amount of retarder added increases with the increase in temperature. However, due to the influence of the underground geothermal gradient, the bottom hole temperature increases with the increase in the depth of the well. The test temperature (i.e., the circulation temperature) for testing the thickening time is generally 0.75-0.9 times the bottom hole static temperature. As a result, after the cement slurry is pumped into place, the top cement slurry static temperature (30-90°C) is much lower than the circulation temperature during the thickening time test, resulting in super-slow setting or long-term non-solidification of the top cement slurry, which seriously affects the cementing quality and well construction cycle. If there is a gas layer in the top layer of the cementing, it may lead to cementing failure, and in severe cases, a blowout accident may occur. When the circulation temperature is below 110°C, the existing retarder basically meets the construction requirements, but when it is higher than 110°C, the prepared cement slurry is prone to super-slow setting.

[0003] Therefore, it is urgent to develop an oil well cement retarder suitable for long sealing section cementing at above 110°C, shorten the waiting time of cement slurry at the top of long sealing section cementing, solve the problem of super slow setting or long-term non-setting of cement slurry at the top of long sealing section cementing, so as to meet the cementing construction needs of long sealing section in deep wells and ultra-deep wells. Summary of the invention

[0004] Aiming at the problems that the top of the oil well cement slurry prepared by using the existing retarder has super-slow setting and slow strength development in the long sealing section cementing, and the existing retarder is easy to destroy the water loss performance of the oil well cement slurry, the present invention provides a polymer and a preparation method thereof, a retarder and the oil well cement slurry.

[0005] In order to achieve the above object, the present invention provides a polymer in a first aspect, comprising a hydrophilic main chain and end-capping structures at both ends of the hydrophilic main chain; wherein:

[0006] The hydrophilic main chain contains structural unit A, structural unit B and structural unit C;

[0007] The structural unit A has a structure shown in formula (1); the structural unit B has a structure shown in formula (2); the structural unit C has a structure shown in formula (3);

[0008]

[0009] Wherein, R1, R2, R3, R4, and R5 are each independently selected from -H or C 1- C2 alkyl; R6 is selected from C1-C3 alkylene; Z is selected from H + , K + 、Na + or NH4 + ; R7, R8, R9, R 10 Each independently selected from -H, -CH3, -COOM 1 or -CH2COOM 2 , and R7, R8, R9, R 10 are not simultaneously selected from -H or -CH3; wherein M 1 、M 2 Each independently selected from H + , K + 、Na + or NH4 + ; R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from -H or C 1- C2 alkyl;

[0010] The molar ratio of the structural unit A: structural unit B: structural unit C is 10: (0.5-8): (0.1-4);

[0011] The end-capping structure has a structure shown in formula (4);

[0012]

[0013] Wherein, Q1, Q2 and Q3 are polymer segments, and Q1, Q2 and Q3 each independently contain a structural unit D and a structural unit E; wherein the structural unit D has a structure shown in formula (5); and the structural unit E has a structure shown in formula (6);

[0014]

[0015] Among them, R 16 , R17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 Each is independently selected from -H or -CH3;

[0016] The molar ratio of the structural unit D:structural unit E is 1:(0.5-5).

[0017] The second aspect of the present invention provides a method for preparing a polymer, comprising: in the presence of a first solvent, polymerizing a monomer A', a monomer B', a monomer C' and an initiator G to obtain a polymer;

[0018] Wherein, the monomer A' has a structure shown in formula (7); the monomer B' has a structure shown in formula (8); and the monomer C' has a structure shown in formula (9);

[0019]

[0020] Wherein, R1, R2, R3, R4, and R5 are each independently selected from -H or C 1- C2 alkyl; R6 is selected from C1-C3 alkylene; Z is selected from H + , K + 、Na + or NH4 + ; R7, R8, R9, R 10 Each independently selected from -H, -CH3, -COOM 1 or -CH2COOM 2 , and R7, R8, R9, R 10 are not simultaneously selected from -H or -CH3; wherein M 1 、M 2 Each independently selected from H + , K + 、Na + or NH4 + ; R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from -H or C 1- C2 alkyl;

[0021] The initiator G has a structure shown in formula (10);

[0022]

[0023] Wherein, Q1, Q2, Q3, Q4, Q5, Q6 are polymer segments, and Q1, Q2, Q3, Q4, Q5, Q6 each independently contain a structural unit D and a structural unit E; wherein the structural unit D has a structure shown in formula (11); and the structural unit E has a structure shown in formula (12);

[0024]

[0025] Among them, R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 Each is independently selected from -H or -CH3;

[0026] The molar ratio of the structural unit D: structural unit E is 1: (0.5-5);

[0027] The molar ratio of the monomer A':monomer B':monomer C':initiator G is 10:(0.5-8):(0.1-4):(0.5-2).

[0028] The third aspect of the present invention provides a polymer obtained by the preparation method described in the second aspect.

[0029] A fourth aspect of the present invention provides a retarder, comprising: a main polymer and a cosolvent;

[0030] Wherein, the weight ratio of the main polymer:cosolvent is 10:(0.4-2);

[0031] The main polymer is the polymer described in the first aspect or the third aspect.

[0032] The fifth aspect of the present invention provides an oil well cement slurry, comprising the retarder described in the fourth aspect.

[0033] Through the above technical solution, the present invention has the following beneficial effects:

[0034] (1) The polymer provided by the present invention adopts a main chain containing sulfonic acid groups, amide groups and carboxyl groups. These hydrophilic groups provide the polymer with excellent water solubility and ion complexing ability, and the end-capping structures at both ends of the main chain have multiple branches, thereby forming a polymer structure with temperature-sensitive water solubility, so that the polymer has excellent ability to promote cement slurry retarding at high temperature, and as the temperature decreases, the retarding ability weakens. The retarder with the polymer as the main component can accelerate the strength development of the top oil well cement slurry in the long sealing section cementing, and achieve the top cement slurry compressive strength of 7MPa or more at 80°C for 48h;

[0035] (2) The polymer provided by the present invention has good compatibility through the design of the main chain and the end-capping structure, and will not produce competitive adsorption with the polymer fluid loss reducer in the oil well cement slurry, and has little effect on the water loss of the oil well cement slurry, which is beneficial to the cement slurry formula design and on-site promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the infrared spectrum of polymer P1 prepared in Example 1 of the present invention.

[0037] Figure 2 The thickening curve of the experimental oil well cement slurry at 125° C. using the retarder S1 (containing the polymer prepared in Example 1) provided by the present invention.

[0038] Figure 3 The compressive strength development curve of the experimental oil well cement slurry at 80° C. using the retarder S1 (containing the polymer prepared in Example 1) provided by the present invention.

[0039] Figure 4 The compressive strength development curve of the experimental oil well cement slurry at 30° C. using the retarder S1 (containing the polymer prepared in Example 1) provided by the present invention.

[0040] Figure 5 It is the thickening curve of the experimental oil well cement slurry using retarder DS1 (containing the polymer prepared in Comparative Example 1) at 125°C.

[0041] Figure 6 The compressive strength development curve of the experimental oil well cement slurry using retarder DS1 (containing the polymer prepared in Comparative Example 1) at 80°C. DETAILED DESCRIPTION

[0042] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0043] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0044] The first aspect of the present invention provides a polymer, comprising a hydrophilic main chain and end-capping structures at both ends of the hydrophilic main chain; wherein:

[0045] The hydrophilic main chain contains structural unit A, structural unit B and structural unit C;

[0046] The structural unit A has a structure shown in formula (1); the structural unit B has a structure shown in formula (2); the structural unit C has a structure shown in formula (3);

[0047]

[0048] Wherein, R1, R2, R3, R4, and R5 are each independently selected from -H or C 1- C2 alkyl; R6 is selected from C1-C3 alkylene; Z is selected from H + , K + 、Na + or NH4 + ; R7, R8, R9, R 10 Each independently selected from -H, -CH3, -COOM 1 or -CH2COOM 2 , and R7, R8, R9, R 10 are not simultaneously selected from -H or -CH3; wherein M 1 、M 2 Each independently selected from H + , K + 、Na + or NH4 + ; R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from -H or C 1- C2 alkyl;

[0049] The molar ratio of the structural unit A: structural unit B: structural unit C is 10: (0.5-8): (0.1-4);

[0050] The end-capping structure has a structure shown in formula (4);

[0051]

[0052] Wherein, Q1, Q2 and Q3 are polymer segments, and Q1, Q2 and Q3 each independently contain a structural unit D and a structural unit E; wherein the structural unit D has a structure shown in formula (5); and the structural unit E has a structure shown in formula (6);

[0053]

[0054] Among them, R 16 , R 17 , R18 , R 19 , R 20 , R 21 , R 22 , R 23 Each is independently selected from -H or -CH3;

[0055] The molar ratio of the structural unit D:structural unit E is 1:(0.5-5).

[0056] According to the present invention, the hydrophilic main chain of the polymer contains specific structural units A, B and C, wherein the structural unit A contains a sulfonic acid group, the structural unit B contains a carboxyl group, and the structural unit C contains an amide group. Under the joint action of the hydrophilic sulfonic acid group, carboxyl group and amide group, the main chain has excellent water solubility and ion complexing ability, which is beneficial to improving the retarding ability of the polymer in oil well cement slurry and reducing the damage to the water loss performance of the oil well cement slurry.

[0057] According to the present invention, in the structural unit A of the hydrophilic main chain, preferably, R1, R2, R3, R4, and R5 are each independently selected from -H or -CH3; R6 is -CH2-, which is more conducive to improving the stability of the polymer molecular structure and improving the chemical stability of the polymer under high temperature and high alkalinity conditions of oil well cement slurry.

[0058] According to the present invention, in the structural unit B of the hydrophilic main chain, R7, R8, R9, R 10 Meeting the above-defined range is beneficial to improving the polymer's adsorption and complexing ability for calcium ions, cement particles and hydration products in oil well cement slurry.

[0059] According to the present invention, in the structural unit C of the hydrophilic main chain, preferably, R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from -H or -CH3 is more conducive to improving the liquid phase viscosity of the polymer in the oil well cement slurry, and assisting the water loss reduction performance, reducing the competitive adsorption between the polymer and the water loss reducer in the oil well cement slurry, and thus reducing the damage to the water loss performance of the oil well cement slurry.

[0060] According to the present invention, on the basis of satisfying the above ratio, preferably, the molar ratio of structural unit A, structural unit B and structural unit C in the hydrophilic main chain is 10:(1-6):(1-3), which can further balance the effects of the polymer on the retarding properties and water loss properties of oil well cement slurry.

[0061] According to the present invention, both ends of the main chain of the polymer have specific end-capping structures, as shown in formula (4), in which the end-capping structure is adjacent to the main chain and is a benzene ring, and the carbon atoms at positions 3, 4 and 5 of the benzene ring are connected to the side chain through ether bonds (the positions of the ether bonds are shown in (5) and the structural unit shown in formula (6)), respectively, and the side chain contains polymer segments Q1, Q2 or Q3, respectively, and the terminal carbon atom of the side chain is connected to a hydroxyl group. By adopting such a structural design, the end-capping structure can have a temperature-sensitive property, so that the polymer can exhibit different conformations in water with temperature changes, and thus exhibit different degrees of retarding properties. Specifically, it can have excellent retarding properties under high temperature conditions (for example, the bottom of a long sealing section cementing well), delaying the thickening of the oil well cement slurry at the bottom, and can have relatively reduced retarding properties under relatively low temperature conditions (for example, the top oil well cement slurry position of a long sealing section cementing well), promoting the strength development of the top cement slurry.

[0062] According to the present invention, in the end-capping structure of the polymer, the polymer segments Q1, Q2 and Q3 are independent of each other and may be the same or different, preferably the same.

[0063] According to the present invention, in the polymer segments Q1, Q2 and Q3, the structural unit D and the structural unit E together form an amphiphilic thermosensitive polyether segment, thereby making the polymer have thermosensitive properties. Preferably, the molar ratio of the structural unit D: structural unit E is 1:(1-3).

[0064] According to the present invention, in the structural unit D, preferably, R 16 , R 17 , R 18 and R 19 It is -H, so that the structural unit D has better hydrophilicity and provides a hydrophilic segment in the amphiphilic temperature-sensitive polyether segment.

[0065] According to the present invention, in the structural unit E, preferably, R 20 , R 21 and R 22 For -H, R 23 It is -CH3, so that the structural unit E has a certain hydrophobicity and provides a hydrophobic segment in the amphiphilic temperature-sensitive polyether segment.

[0066] According to the present invention, the end-capping structures at both ends of the main chain of the polymer are independent of each other and can be the same or different, as long as they satisfy the structure shown in formula (4). Preferably, the end-capping structures at both ends of the main chain of the polymer are the same.

[0067] According to the present invention, in formula (4), Indicates the connection position between the end-capping structure and the hydrophilic main chain.

[0068] According to the present invention, the weight average molecular weight of the polymer is (10-80)×10 4 g / mol, preferably (30-60)×10 4 g / mol.

[0069] The polymer provided by the present invention has a specific hydrophilic main chain and a multi-branched end-capping structure, wherein the structural unit of the hydrophilic main chain contains a sulfonic acid group, an amide group and a carboxyl group, which gives the main chain excellent water solubility and excellent ion complexing ability, and the end-capping structure has multiple branches, and the hydrophilic main chain and the end-capping structure together form an amphiphilic polymer structure with temperature-sensitive water solubility, so that the polymer has different molecular conformations at different temperatures. When the ambient temperature rises, the solubility of the multi-branched chains at both ends of the polymer deteriorates, and the middle linear chain segment is exposed. In this case, the polymer has excellent oil well cement slurry retarding ability, and as the ambient temperature decreases, the solubility of the multi-branched chains at both ends of the polymer is enhanced, wrapping the middle linear chain segment, in this case, the complexing ability of the polymer deteriorates, the retarding ability is weakened, and the strength development of the oil well cement slurry is beneficial. The retarder with the polymer provided by the present invention as the main component can accelerate the strength development of the top cement slurry under the premise of ensuring the retarding effect of the oil well cement slurry under the circulating temperature conditions in the long sealing section cementing, that is, the top cement slurry is made to solidify quickly under the conditions below the circulating temperature, and the compressive strength of the top cement slurry can reach more than 7MPa at 80°C for 48 hours. In addition, there is a problem of competitive adsorption between conventional polymer retarders and polymer fluid loss reducers in cement slurry, which often causes a large amount of water loss in cement slurry and endangers construction safety. The polymer provided by the present invention, through the main chain functional group and end-capping structure design, will not produce competitive adsorption with the polymer fluid loss reducer in the oil well cement slurry, and has little effect on the water loss of the oil well cement slurry, which is beneficial to the cement slurry formula design and construction safety.

[0070] According to a most preferred embodiment of the present invention, in the polymer, the hydrophilic main chain contains structural unit A Structural unit B and structural unit C The molar ratio of the structural unit A: structural unit B: structural unit C is 10: (3-4): (2-3); in the end-capping structure, Q1, Q2 and Q3 each independently contain structural unit D and structural unit E The molar ratio of the structural unit D: structural unit E is 1: (2-2.5); the weight average molecular weight of the polymer is (40-55)×10 4The polymer of the most preferred embodiment has the effect of further shortening the waiting time of cement slurry at the top of the long sealing section cementing, can better solve the problem of super slow setting of cement slurry at the top, and has better compatibility.

[0071] A second aspect of the present invention provides a method for preparing a polymer, comprising:

[0072] In the presence of a first solvent, monomer A', monomer B', monomer C' and initiator G are polymerized to obtain a polymer;

[0073] Wherein, the monomer A' has a structure shown in formula (7); the monomer B' has a structure shown in formula (8); and the monomer C' has a structure shown in formula (9);

[0074]

[0075] Wherein, R1, R2, R3, R4, and R5 are each independently selected from -H or C 1- C2 alkyl; R6 is selected from C1-C3 alkylene; Z is selected from H + , K + 、Na + or NH4 + ; R7, R8, R9, R 10 Each independently selected from -H, -CH3, -COOM 1 or -CH2COOM 2 , and R7, R8, R9, R 10 are not simultaneously selected from -H or -CH3; wherein M 1 、M 2 Each independently selected from H + , K + 、Na + or NH4 + ; R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from -H or C 1- C2 alkyl;

[0076] The initiator G has a structure shown in formula (10);

[0077]

[0078] Wherein, Q1, Q2, Q3, Q4, Q5, Q6 are polymer segments, and Q1, Q2, Q3, Q4, Q5, Q6 each independently contain a structural unit D and a structural unit E; wherein the structural unit D has a structure shown in formula (11); and the structural unit E has a structure shown in formula (12);

[0079]

[0080] Among them, R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 Each is independently selected from -H or -CH3;

[0081] The molar ratio of the structural unit D: structural unit E is 1: (0.5-5);

[0082] The molar ratio of the monomer A':monomer B':monomer C':initiator G is 10:(0.5-8):(0.1-4):(0.5-2).

[0083] According to the present invention, in the preparation method of the polymer, the monomer A', the monomer B' and the monomer C' are polymerized to form a main chain structure, wherein the monomer A' can provide a sulfonic acid group, the monomer B' can provide a carboxyl group, and the monomer C' can provide an amide group. The hydrophilic groups contained in the above raw material monomers make the main chain structure formed by polymerization have excellent water solubility and ion complexing ability.

[0084] According to the present invention, for the monomer A', preferably, R1, R2, R3, R4, and R5 are each independently selected from -H or -CH3; and R6 is -CH2-.

[0085] According to the present invention, for the monomer C', preferably, R 11 , R 12 , R 13 , R 14 , R 15 Each is independently selected from -H or -CH3.

[0086] According to the present invention, in the method for preparing the polymer, the initiator G can form a capping structure connected to both ends of the main chain structure.

[0087] According to the present invention, in the initiator G, the polymer segments Q1, Q2, Q3, Q4, Q5, and Q6 are independent of each other and may be the same or different, preferably the same.

[0088] According to the present invention, in the structural unit D contained in the initiator G, preferably, R 16 , R 17 , R 18 and R 19 is -H.

[0089] According to the present invention, among the structural units E contained in the initiator G, preferably, R 20 , R 21 and R 22 For -H, R 23 It is -CH3.

[0090] According to the present invention, in the initiator G, the structural unit D and the structural unit E, on the basis of satisfying the above-mentioned proportional relationship, preferably, the molar ratio of the structural unit D:structural unit E is 1:(1-3), which can make the polymer segments Q1, Q2, Q3, Q4, Q5, and Q6 have better amphiphilic thermosensitive properties.

[0091] According to the present invention, preferably, the weight average molecular weight of the initiator G is (0.5-3)×10 4 g / mol.

[0092] According to the present invention, in the preparation method of the polymer, the monomer A', monomer B', monomer C' and initiator G, on the basis of satisfying the above-mentioned feed ratio relationship, preferably, the molar ratio of monomer A': monomer B': monomer C': initiator G is 10: (1-6): (1-3): (1-1.5). By adopting the above-mentioned preferred feed ratio, the influence of the polymer on the slow setting performance and the water loss performance of the oil well cement slurry can be further balanced.

[0093] According to the present invention, in the preparation method of the polymer, the first solvent is selected from alcohol solvents and / or ketone solvents. Preferably, the first solvent can be selected from at least one of methyl isobutyl ketone, ethanol, propanol, butanol and acetone, and more preferably methyl isobutyl ketone.

[0094] According to the present invention, in the method for preparing the polymer, the conditions of the polymerization reaction include: temperature of 60-90° C. and time of 2-4 hours.

[0095] According to a preferred embodiment of the present invention, the operation process of preparing the polymer comprises:

[0096] (I) dividing the first solvent into two parts, a first solvent-i and a first solvent-ii, and mixing the monomer A', the monomer B', the monomer C', the initiator G and the first solvent-i to obtain a mixed solution;

[0097] (II) heating the first solvent-ii to a temperature required for a polymerization reaction, and then adding the mixed solution to carry out a polymerization reaction to obtain a reaction product system;

[0098] (III) separating and treating the reaction product system to obtain the polymer.

[0099] According to the present invention, in step (I), preferably, the molar ratio of the first solvent-i:first solvent-ii is 1:(0.5-5).

[0100] According to the present invention, in step (II), preferably, the mixed solution is added to the first solvent-ii heated to the required temperature for the polymerization reaction in a uniform dripping manner, the dripping process lasts for 3-8 hours, and then the polymerization reaction is carried out by keeping warm for 2-4 hours.

[0101] According to the present invention, in step (III), preferably, the separation treatment is carried out by vacuum distillation to separate and remove the first solvent in the reaction product system to obtain the target polymer.

[0102] In the present invention, the preparation method of the initiator G comprises:

[0103] (1) in the presence of a first catalyst, subjecting 5-bromo-1,2,3-pyrogallol to a first reaction with monomer D' and monomer E' to obtain a first product;

[0104] Wherein, the monomer D' has a structure shown in formula (13); the monomer E' has a structure shown in formula (14);

[0105]

[0106] Among them, R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 Each is independently selected from -H or -CH3;

[0107] (2) in the presence of a second solvent, subjecting the first product to a second reaction with metal powder L to obtain a second product; subjecting the second product to a third reaction with carbon dioxide to obtain a third product; and subjecting the third product to a fourth reaction in the presence of an acid, and separating the resulting product system to obtain a fourth product;

[0108] (3) in the presence of a third solvent, subjecting the fourth product to a fifth reaction with thionyl chloride to obtain a fifth product;

[0109] (4) subjecting the fifth product to a sixth reaction with hydrogen peroxide to obtain the initiator G.

[0110] According to the present invention, in step (1), the main process of the first reaction is as follows:

[0111]

[0112] Among them, Q1, Q2 and Q3 each independently contain structural units and structural units Among them, R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 Each is independently selected from -H or -CH3.

[0113] According to the present invention, in step (1), preferably, the first catalyst and 5-bromo-1,2,3-pyrogallol are mixed, and then the monomer D' and monomer E are added to carry out the first reaction to obtain a viscous first product.

[0114] According to the present invention, in step (1), the first catalyst can be selected from at least one of boron trifluoride-ether complex, sodium hydroxide and potassium hydroxide.

[0115] According to the present invention, in step (1), the molar ratio of 5-bromo-1,2,3-pyrogallol: first catalyst: monomer D': monomer E' is 1: (0.01-0.05): (1-3): (3-9).

[0116] According to the present invention, in step (1), the conditions of the first reaction include: temperature of 100-150° C., pressure of 2.5-3 MPa, and time of 2-5 h.

[0117] According to the present invention, in step (2), the main process of the second reaction is as follows:

[0118]

[0119] According to the present invention, in step (2), preferably, the second solvent is mixed with the metal powder L, and then the first product is added to carry out the second reaction.

[0120] According to the present invention, in step (2), the main process of the third reaction is as follows:

[0121]

[0122] According to the present invention, in step (2), preferably, carbon dioxide is introduced into the product system obtained by the second reaction, so that the second product undergoes a third reaction with carbon dioxide.

[0123] According to the present invention, in step (2), the main process of the fourth reaction is as follows:

[0124]

[0125] According to the present invention, in step (2), preferably, after the third reaction is completed, an acid solution (such as aqueous hydrochloric acid solution) is added to adjust the pH value of the reaction product system to 2-4, and a fourth reaction (hydrolysis reaction) is carried out, and then the mixture is allowed to stand for stratification, and a precipitate phase is separated to obtain the fourth product.

[0126] According to the present invention, in step (2), the second solvent may be an ether solvent. Preferably, the second solvent may be selected from at least one of tetrahydrofuran, diethyl ether, dibutyl ether and dipentyl ether.

[0127] According to the present invention, in step (2), the metal powder L can be selected from magnesium powder or zinc powder.

[0128] According to the present invention, in step (2), when all the second product obtained from the second reaction participates in the third reaction, preferably, the molar ratio of the first product: metal powder L: carbon dioxide is 1:(1-2):(2-4).

[0129] According to the present invention, in step (2), the conditions of the second reaction include: temperature of -5-0°C and time of 3-5h.

[0130] According to the present invention, in step (2), the conditions of the third reaction include: temperature of -5-0°C and time of 2-8h.

[0131] According to the present invention, in step (2), the conditions of the fourth reaction include: temperature of 0-10°C, pH of 2-4, and time of 4-5h.

[0132] According to the present invention, in step (3), the main process of the fifth reaction is as follows:

[0133]

[0134] According to the present invention, in step (3), preferably, the fourth product, thionyl chloride and the third solvent are mixed and heated under reflux reaction to obtain the fifth product.

[0135] According to the present invention, in step (3), the third solvent may be a benzene solvent. Preferably, the third solvent may be selected from at least one of benzene, toluene, ethylbenzene and xylene.

[0136] According to the present invention, in step (3), the molar ratio of the fourth product to thionyl chloride is 1:(5-7).

[0137] According to the present invention, in step (3), the conditions of the fifth reaction include: temperature of 80-150° C. and time of 5-8 h.

[0138] According to the present invention, in step (4), the main process of the sixth reaction is as follows:

[0139]

[0140] According to the present invention, in step (4), preferably, the fifth product is mixed with an aqueous hydrogen peroxide solution, the resulting mixture is added to an aqueous solution of a co-solvent, the temperature is raised to the required reaction temperature to carry out the sixth reaction, and the product is filtered to obtain the initiator G.

[0141] According to the present invention, in step (4), the molar ratio of the fifth product to hydrogen peroxide is 1:(1.5-2).

[0142] According to the present invention, in step (4), the cosolvent may be a composite reagent of a surfactant and a soluble carbonate; wherein the surfactant is preferably at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and sodium dodecyl diphenyl ether disulfonate; and the soluble carbonate is preferably sodium carbonate and / or potassium carbonate.

[0143] According to the present invention, preferably, in the aqueous solution of the co-solvent, the weight ratio of the surfactant: the soluble carbonate: water is (0.5-5): (15-20):100.

[0144] According to the present invention, in step (4), the conditions of the sixth reaction include: temperature of 30-40° C. and time of 2-4 h.

[0145] The invention carries out polymerization reaction of a specific monomer A' capable of providing a sulfonic acid group, a monomer B' capable of providing a carboxyl group, a monomer C' capable of providing an amide group and an initiator G having a specific multi-branched structure, so as to obtain a polymer having a hydrophilic main chain and multi-branched end-capping structures at both ends of the hydrophilic main chain, wherein the hydrophilic main chain and the multi-branched end-capping structures volatilize together, so that the prepared polymer has excellent retarding ability of oil well cement slurry at high temperature, and the retarding ability weakens as the temperature decreases. The polymer, as a retarder component, can accelerate the strength development of top cement slurry under the premise of ensuring the retarding effect of oil well cement slurry under cyclic temperature conditions, so that the compressive strength of the top cement slurry at 80°C for 48 hours reaches more than 7MPa, and the polymer has good compatibility and little effect on the water loss of oil well cement slurry.

[0146] The third aspect of the present invention provides a polymer obtained by the preparation method described in the second aspect.

[0147] According to the present invention, the structure, parameters and properties of the polymer prepared by the method described in the second aspect are the same as those of the polymer described in the first aspect of the present invention, and will not be described in detail here.

[0148] A fourth aspect of the present invention provides a retarder, comprising: a main polymer and a cosolvent;

[0149] Wherein, the weight ratio of the main polymer:cosolvent is 10:(0.4-2);

[0150] The main polymer is the polymer described in the first aspect or the third aspect.

[0151] According to the present invention, in the retarder, the co-solvent may be selected from alcohols and / or ketones, preferably at least one of ethanol, isopropanol, butanol and methyl isobutyl ketone.

[0152] According to the present invention, the retarder can be prepared by mixing the main polymer and the auxiliary agent according to the above ratio.

[0153] The retarder provided by the present invention uses the specific polymer provided by the present invention as the main functional component, and is a new type of retarder that can make cement slurry solidify quickly under conditions lower than the circulating temperature. The retarder is applied to cementing of long sealing sections, and can accelerate the strength development of top cement slurry while ensuring the retarding effect of bottom oil well cement slurry, so that the compressive strength of top cement slurry can reach more than 7MPa at 80°C for 48h, and the retarder has good compatibility and has little effect on the water loss of oil well cement slurry.

[0154] According to the present invention, preferably, the retarder is prepared into a solution with water before use, and is used in the form of an aqueous solution and added to the oil well cement slurry. Preferably, in the aqueous solution of the retarder, the weight ratio of the main polymer: the cosolvent: water is 10: (0.4-2): (20-30).

[0155] The fifth aspect of the present invention provides an oil well cement slurry, comprising the retarder described in the fourth aspect.

[0156] According to the present invention, the components of the oil well cement slurry, in addition to the oil well cement and the retarder, may also include various conventional oil well cement slurry admixtures in the art, including but not limited to weighting agents, lightening agents, fluid loss additives, drag reducing agents, defoaming agents, etc.

[0157] According to the present invention, the content of the retarder in the oil well cement slurry is not particularly limited. In some embodiments of the present invention, preferably, in the oil well cement slurry, the weight ratio of the retarder to the oil well cement in the oil well cement slurry is (1-8):100.

[0158] The present invention will be described in detail below by way of examples. In the following preparation examples, examples and comparative examples, unless otherwise specified, all are conventional methods; the reagents and materials, unless otherwise specified, can be obtained from commercial sources.

[0159] In the following preparation examples and embodiments, the molar ratio of the prepared initiator G and the structural units contained in the polymer is calculated based on the feed amount of the raw materials.

[0160] Preparation Example 1

[0161] This preparation example illustrates the preparation of initiator G.

[0162] (1) 5-bromo-1,2,3-pyrogallol and potassium hydroxide are added to a high-pressure reactor and mixed, nitrogen is introduced to maintain a pressure of 3 MPa, monomer D' (ethylene oxide) is introduced to react for 3 h (reaction temperature is 110° C.), and then monomer E' (propylene oxide) is introduced to react for 3 h (reaction temperature is 110° C.), to obtain a viscous first product;

[0163] Wherein, the molar ratio of 5-bromo-1,2,3-benzenetriol: potassium hydroxide: monomer D': monomer E' is 1:0.03:2:5;

[0164] (2) adding magnesium powder to anhydrous tetrahydrofuran, cooling to 0°C in an ice-water bath for 4 hours, then maintaining 0°C and introducing carbon dioxide gas into the reaction system for 6 hours; after the reaction, slowly adding a 10 wt% hydrochloric acid aqueous solution to the reaction product system, while maintaining the temperature of the reaction system in the range of 0-10°C, the pH value of the reaction system is 3, and the reaction time is 4 hours; then standing and stratifying, collecting the precipitate phase, and obtaining a second product;

[0165] The molar ratio of the first product: magnesium powder: carbon dioxide is 1:1.5:3;

[0166] (3) adding the second product to toluene, then adding thionyl chloride, heating to reflux at 110° C. for 6 h, and removing toluene by distillation under reduced pressure after the reaction to obtain a third product;

[0167] Wherein, the molar ratio of the second product to thionyl chloride is 1:6;

[0168] (4) The third product and the aqueous solution of hydrogen peroxide are mixed evenly, and slowly added dropwise to the aqueous solution of the cosolvent (the weight ratio of sodium dodecylbenzene sulfonate: sodium carbonate: water is 1:18:100), and the addition is completed within 30 minutes. After the addition is completed, the temperature is raised to 40° C. to react for 4 hours. The reaction product is filtered to obtain a solid, and the solid is rinsed with deionized water and dried to obtain initiator G-1;

[0169] Among them, the molar ratio of the third product: hydrogen peroxide: sodium carbonate is 1:1.7:2.

[0170] G-1 has the structure shown in formula (10), and the structural units in the polymer segments Q1, Q2, Q3, Q4, Q5, and Q6 in G-1 are calculated by the feed amount of the raw materials. Structural unit The molar ratio is 1:2.5.

[0171] The weight average molecular weight of G-1 is 1.2×10 4 g / mol.

[0172] Preparation Example 2

[0173] This preparation example illustrates the preparation of initiator G.

[0174] According to the method of Preparation Example 1, the difference is that the monomer D' is (1,2-dimethylethylene oxide) and the monomer E' is (methylpropylene oxide). Other conditions and steps are the same as Preparation Example 1 to obtain initiator G-2.

[0175] G-2 has a structure shown in formula (10), and the structural units in the polymer segments Q1, Q2, Q3, Q4, Q5, and Q6 in G-2 are calculated by the feed amount of the raw materials. Structural unit The molar ratio is 1:2.5.

[0176] The weight average molecular weight of G-2 is 2.2×10 4 g / mol.

[0177] Preparation Example 3

[0178] This preparation example illustrates the preparation of initiator G.

[0179] According to the method of Preparation Example 1, the difference is that the molar ratio of 5-bromo-1,2,3-benzenetriol: potassium hydroxide: monomer D' (ethylene oxide): monomer E' (propylene oxide) is 1:0.03:3:3, and other conditions and steps are the same as Preparation Example 1 to obtain initiator G-3.

[0180] G-3 has a structure shown in formula (10), and the structural units in the polymer segments Q1, Q2, Q3, Q4, Q5, and Q6 in G-3 are calculated by the feed amount of the raw materials. Structural unit The molar ratio is 1:1.

[0181] The weight average molecular weight of G-3 is 0.8×10 4 g / mol.

[0182] Preparation Example 4

[0183] This preparation example illustrates the preparation of initiator G.

[0184] According to the method of Preparation Example 1, the difference is that the molar ratio of 5-bromo-1,2,3-benzenetriol: potassium hydroxide: monomer D' (ethylene oxide): monomer E' (propylene oxide) is 1:0.03:6:3, and other conditions and steps are the same as Preparation Example 1 to obtain initiator G-4.

[0185] G-4 has a structure shown in formula (10), and the structural units in the polymer segments Q1, Q2, Q3, Q4, Q5, and Q6 in G-4 are calculated by the feed amount of the raw materials. Structural unit The molar ratio is 1:0.5.

[0186] The weight average molecular weight of G-4 is 1.5×10 4 g / mol.

[0187] Preparation Example 5

[0188] This preparation example illustrates the preparation of initiator G.

[0189] The method of Preparation Example 1 was followed, except that the order of introducing monomer D' (ethylene oxide) and monomer E' (propylene oxide) was changed in step (1), that is, monomer E' was introduced first and reacted for 3 h, and then monomer D' was introduced and reacted for 3 h. Other conditions and steps were the same as those of Preparation Example 1, to obtain initiator G-5.

[0190] G-5 has the structure shown in formula (10), and the structural units in the polymer segments Q1, Q2, Q3, Q4, Q5, and Q6 in G-4 are calculated by the feed amount of the raw materials. Structural unit The molar ratio is 1:0.5.

[0191] The weight average molecular weight of G-5 is 1.8×10 4 g / mol.

[0192] Example 1

[0193] This example illustrates the preparation of the polymer

[0194] (I) Methyl isobutyl ketone is divided into two parts: a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i to the first solvent-ii is 1:1.5), and monomer A' (2-acrylamide-2-methylpropanesulfonic acid, i.e. ), monomer B' (itaconic acid, i.e. ), monomer C'(N,N-dimethylacrylamide, i.e. ), initiator G-1 is added into the first solvent-i and mixed evenly to obtain a mixed solution;

[0195] Wherein, the molar ratio of monomer A':monomer B':monomer C':initiator G-1:first solvent-i is 10:3:2:1.2:35;

[0196] (II) adding the first solvent-ii into a reactor, raising the temperature to 80° C., then uniformly dropping the mixed solution into the first solvent-ii at 80° C., the dropping process lasts for 4 hours, and then keeping the temperature for 4 hours to carry out polymerization reaction to obtain a reaction product system;

[0197] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as P1).

[0198] The infrared spectrum test of P1 shows the following results: Figure 1 As shown, the stretching vibration absorption peak of the amide group is at 3464.1 cm -1 The carbonyl -C=O stretching vibration absorption peaks of the amide group and the carboxyl group in itaconic acid are at 1641.4 cm -1 Sulfonic acid -SO3 - The stretching vibration absorption peak is at 1224.7 cm -1 The -CO- stretching vibration and bending vibration absorption peaks of the polyether segment are at 1039.6 cm -1 881cm -1 At this point, all the functional groups in the raw material monomers appear in the infrared spectrum of the polymer, indicating that the polymerization is successfully initiated and the polymer of the present invention is prepared.

[0199] In P1, the structural unit A in the hydrophilic main chain Structural unit B Structural unit C The molar ratio is 10:3:2; the structural unit D in the end-capping structure Structural unit E The molar ratio of P1 is 1:2.5; the weight average molecular weight of P1 is 53×10 4 g / mol.

[0200] Example 2

[0201] This example illustrates the preparation of the polymer

[0202] (I) Methyl isobutyl ketone is divided into two parts: a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i to the first solvent-ii is 1:1.5), and monomer A' (2-acrylamide-2-methylpropanesulfonic acid, i.e. ), monomer B' (maleic acid, i.e. ), monomer C'(N,N-dimethylacrylamide, i.e. ), initiator G-1 is added into the first solvent-i and mixed evenly to obtain a mixed solution;

[0203] Wherein, the molar ratio of monomer A':monomer B':monomer C':initiator G-1:first solvent-i is 10:4:3:1.2:35;

[0204] (II) adding the first solvent-ii into a reactor, raising the temperature to 80° C., then uniformly dropping the mixed solution into the first solvent-ii at 80° C., the dropping process lasts for 4 hours, and then keeping the temperature for 4 hours to carry out polymerization reaction to obtain a reaction product system;

[0205] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as P2).

[0206] In P2, the structural unit A in the hydrophilic main chain ( Structural unit B( Structural unit C The molar ratio is 10:4:3; the structural unit D in the end-capping structure Structural unit E The molar ratio of P2 is 1:2.5; the weight average molecular weight of P2 is 41×10 4 g / mol.

[0207] Example 3

[0208] This example illustrates the preparation of the polymer

[0209] (I) Methyl isobutyl ketone is divided into two parts: a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i to the first solvent-ii is 1:2), and monomer A' (2-acrylamide-2-methylpropanesulfonic acid, i.e. ), monomer B' (sodium methacrylate, i.e. ), monomer C' acrylamide (acrylamide, i.e. ), initiator G-1 is added into the first solvent-i and mixed evenly to obtain a mixed solution;

[0210] Wherein, the molar ratio of monomer A':monomer B':monomer C':initiator G-1:first solvent-i is 10:0.6:4:1.5:30;

[0211] (II) adding the first solvent-ii into a reactor, raising the temperature to 80° C., then uniformly dropping the mixed solution into the first solvent-ii at 80° C., the dropping process lasts for 4 hours, and then keeping the temperature for 4 hours to carry out polymerization reaction to obtain a reaction product system;

[0212] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as P3).

[0213] In P3, the structural unit A in the hydrophilic main chain Structural unit B Structural unit C The molar ratio is 10:0.6:4; the structural unit D in the end-capping structure Structural unit E The molar ratio of P3 is 1:2.5; the weight average molecular weight of P3 is 15×10 4 g / mol.

[0214] Example 4

[0215] This example illustrates the preparation of the polymer

[0216] (I) Methyl isobutyl ketone is divided into two parts: a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i to the first solvent-ii is 1:3), and monomer A' (2-acrylamide-2-methylpropanesulfonic acid, i.e. ), monomer B' (acrylic acid, i.e. ), monomer C' (methacrylamide, i.e. ), initiator G-1 is added into the first solvent-i and mixed evenly to obtain a mixed solution;

[0217] Wherein, the molar ratio of monomer A':monomer B':monomer C':initiator G-1:first solvent-i is 10:7:0.5:1:35;

[0218] (II) adding the first solvent-ii into a reactor, raising the temperature to 90° C., then uniformly dropping the mixed solution into the first solvent-ii at 90° C., the dropping process lasts for 3 hours, and then keeping the temperature for 3 hours to carry out polymerization reaction to obtain a reaction product system;

[0219] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as P4).

[0220] In P4, the structural unit A in the hydrophilic main chain Structural unit B Structural unit C The molar ratio is 10:7:0.5; the structural unit D in the end-capping structure Structural unit E The molar ratio of P4 is 1:2.5; the weight average molecular weight of P4 is 24×10 4 g / mol.

[0221] Example 5

[0222] This example illustrates the preparation of the polymer

[0223] (I) Methyl isobutyl ketone is divided into two parts: a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i to the first solvent-ii is 1:3), and monomer A' (2-acrylamide-2-methylpropanesulfonic acid, i.e. ), monomer B' (acrylic acid, i.e. ), monomer C' (methacrylamide, i.e. ), initiator G-1 is added into the first solvent-i and mixed evenly to obtain a mixed solution;

[0224] Wherein, the molar ratio of monomer A':monomer B':monomer C':initiator G-1:first solvent-i is 10:8:4:1:35;

[0225] (II) adding the first solvent-ii into a reactor, raising the temperature to 90° C., then uniformly dropping the mixed solution into the first solvent-ii at 90° C., the dropping process lasts for 3 hours, and then keeping the temperature for 3 hours to carry out polymerization reaction to obtain a reaction product system;

[0226] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as P5).

[0227] In P5, the structural unit A in the hydrophilic main chain Structural unit B Structural unit C The molar ratio is 10:8:4; the structural unit D in the end-capping structure Structural unit E The molar ratio of P5 is 1:2.5; the weight average molecular weight of P5 is 30×10 4 g / mol.

[0228] Example 6

[0229] This example illustrates the preparation of the polymer

[0230] (I) Methyl isobutyl ketone is divided into two parts: a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i to the first solvent-ii is 1:3), and monomer A' (2-acrylamide-2-methylpropanesulfonic acid, i.e. ), monomer B' (acrylic acid, i.e. ), monomer C' (methacrylamide, i.e. ), initiator G-2 is added to the first solvent-i and mixed evenly to obtain a mixed solution;

[0231] Wherein, the molar ratio of monomer A':monomer B':monomer C':initiator G-2:first solvent-i is 10:7:0.5:1:35;

[0232] (II) adding the first solvent-ii into a reactor, raising the temperature to 90° C., then uniformly dropping the mixed solution into the first solvent-ii at 90° C., the dropping process lasts for 3 hours, and then keeping the temperature for 3 hours to carry out polymerization reaction to obtain a reaction product system;

[0233] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as P6).

[0234] In P6, the structural unit A in the hydrophilic main chain Structural unit B Structural unit C The molar ratio is 10:7:0.5; the structural unit D in the end-capping structure Structural unit E The molar ratio of P6 is 1:2.5; the weight average molecular weight of P6 is 30×10 4 g / mol.

[0235] Example 7

[0236] This example illustrates the preparation of the polymer

[0237] (I) Methyl isobutyl ketone is divided into two parts: a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i to the first solvent-ii is 1:3), and monomer A' (2-acrylamide-2-methylpropanesulfonic acid, i.e. ), monomer B' (acrylic acid, i.e. ), monomer C' (methacrylamide, i.e. ), initiator G-3 is added to the first solvent-i and mixed evenly to obtain a mixed solution;

[0238] Wherein, the molar ratio of monomer A':monomer B':monomer C':initiator G-3:first solvent-i is 10:7:0.5:1:35;

[0239] (II) adding the first solvent-ii into a reactor, raising the temperature to 90° C., then uniformly dropping the mixed solution into the first solvent-ii at 90° C., the dropping process lasts for 3 hours, and then keeping the temperature for 3 hours to carry out polymerization reaction to obtain a reaction product system;

[0240] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as P7).

[0241] In P7, the structural unit A in the hydrophilic main chain Structural unit B Structural unit C The molar ratio is 10:7:0.5; the structural unit D in the end-capping structure Structural unit E The molar ratio of P7 is 1:1; the weight average molecular weight of P7 is 42×10 4 g / mol.

[0242] Example 8

[0243] This example illustrates the preparation of the polymer

[0244] (I) Methyl isobutyl ketone is divided into two parts: a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i to the first solvent-ii is 1:3), and monomer A' (2-acrylamide-2-methylpropanesulfonic acid, i.e. ), monomer B' (acrylic acid, i.e. ), monomer C' (methacrylamide, i.e. ), initiator G-4 is added into the first solvent-i and mixed evenly to obtain a mixed solution;

[0245] Wherein, the molar ratio of monomer A':monomer B':monomer C':initiator G-4:first solvent-i is 10:7:0.5:1:35;

[0246] (II) adding the first solvent-ii into a reactor, raising the temperature to 90° C., then uniformly dropping the mixed solution into the first solvent-ii at 90° C., the dropping process lasts for 3 hours, and then keeping the temperature for 3 hours to carry out polymerization reaction to obtain a reaction product system;

[0247] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as P8).

[0248] In P8, the structural unit A in the hydrophilic main chain Structural unit B Structural unit C The molar ratio is 10:7:0.5; the structural unit D in the end-capping structure Structural unit E The molar ratio of P8 is 1:0.5; the weight average molecular weight of P8 is 35×10 4 g / mol.

[0249] Example 9

[0250] This example illustrates the preparation of the polymer

[0251] (I) Methyl isobutyl ketone is divided into two parts: a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i to the first solvent-ii is 1:3), and monomer A' (2-acrylamide-2-methylpropanesulfonic acid, i.e. ), monomer B' (acrylic acid, i.e. ), monomer C' (methacrylamide, i.e. ), initiator G-5 is added to the first solvent-i and mixed evenly to obtain a mixed solution;

[0252] Wherein, the molar ratio of monomer A':monomer B':monomer C':initiator G-5:first solvent-i is 10:7:0.5:1:35;

[0253] (II) adding the first solvent-ii into a reactor, raising the temperature to 90° C., then uniformly dropping the mixed solution into the first solvent-ii at 90° C., the dropping process lasts for 3 hours, and then keeping the temperature for 3 hours to carry out polymerization reaction to obtain a reaction product system;

[0254] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as P9).

[0255] In P9, the structural unit A in the hydrophilic main chain Structural unit B Structural unit C The molar ratio is 10:7:0.5; the structural unit D in the end-capping structure Structural unit E The molar ratio of P9 is 1:0.5; the weight average molecular weight of P9 is 48×10 4 g / mol.

[0256] Comparative Example 1

[0257] Dissolve monomer A' (2-acrylamide-2-methylpropanesulfonic acid), monomer B' (itaconic acid), and monomer C' (N,N-dimethylacrylamide) in deionized water to obtain a mixed solution;

[0258] The mixed solution was heated to 80°C, ammonium persulfate was added, and the temperature was maintained at 80°C for polymerization for 4 hours to obtain a polymer (denoted as D1);

[0259] Wherein, the molar ratio of monomer A':monomer B':monomer C':ammonium persulfate:deionized water is 10:3:2:1.2:60;

[0260] In D1, structural unit A Structural unit B Structural unit C The molar ratio of D1 is 10:3:2; the weight average molecular weight of D1 is 43×10 4 g / mol.

[0261] Comparative Example 2

[0262] (I) dividing methyl isobutyl ketone into two parts, namely a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i to the first solvent-ii is 1:1.5), and adding monomer B' (itaconic acid), monomer C' (N,N-dimethylacrylamide), and initiator G-1 into the first solvent-i and mixing them evenly to obtain a mixed solution;

[0263] Wherein, the molar ratio of monomer B':monomer C':initiator G-1:first solvent-i is 3:2:1.2:35;

[0264] (II) adding the first solvent-ii into a reactor, raising the temperature to 80° C., then uniformly dropping the mixed solution into the first solvent-ii at 80° C., the dropping process lasts for 4 hours, and then keeping the temperature for 4 hours to carry out polymerization reaction to obtain a reaction product system;

[0265] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as D2).

[0266] In D2, the structural unit B in the hydrophilic main chain Structural unit C The molar ratio is 3:2; the structural unit D in the end-capping structure Structural unit E The molar ratio of D2 is 1:2.5; the weight average molecular weight of D2 is 48×10 4 g / mol.

[0267] Comparative Example 3

[0268] (I) dividing methyl isobutyl ketone into two parts, namely a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i: the first solvent-ii is 1:1.5), and adding monomer A' (2-acrylamide-2-methylpropanesulfonic acid), monomer C' (N,N-dimethylacrylamide), and initiator G-1 into the first solvent-i and mixing them evenly to obtain a mixed solution;

[0269] Wherein, the molar ratio of monomer A':monomer C':initiator G-1:first solvent-i is 10:2:1.2:35;

[0270] (II) adding the first solvent-ii into a reactor, raising the temperature to 80° C., then uniformly dropping the mixed solution into the first solvent-ii at 80° C., the dropping process lasts for 4 hours, and then keeping the temperature for 4 hours to carry out polymerization reaction to obtain a reaction product system;

[0271] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as D3).

[0272] In D3, the structural unit A in the hydrophilic main chain Structural unit C The molar ratio is 10:2; the structural unit D in the end-capping structure Structural unit E The molar ratio of D3 is 1:2.5; the weight average molecular weight of D3 is 38×10 4 g / mol.

[0273] Comparative Example 4

[0274] (I) dividing methyl isobutyl ketone into two parts, namely a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i: the first solvent-ii is 1:1.5), and adding monomer A' (2-acrylamide-2-methylpropanesulfonic acid), monomer B' (itaconic acid), and initiator G-1 into the first solvent-i and mixing them evenly to obtain a mixed solution;

[0275] Wherein, the molar ratio of monomer A':monomer B':initiator G-1:first solvent-i is 10:3:1.2:35;

[0276] (II) adding the first solvent-ii into a reactor, raising the temperature to 80° C., then uniformly dropping the mixed solution into the first solvent-ii at 80° C., the dropping process lasts for 4 hours, and then keeping the temperature for 4 hours to carry out polymerization reaction to obtain a reaction product system;

[0277] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as D4).

[0278] In D4, the structural unit A in the hydrophilic main chain Structural unit B The molar ratio is 10:3; the structural unit D in the end-capping structure Structural unit E The molar ratio of P1 is 1:2.5; the weight average molecular weight of P1 is 26×10 4 g / mol.

[0279] Comparative Example 5

[0280] (I) Methyl isobutyl ketone is divided into two parts, namely, a first solvent-i and a first solvent-ii (the molar ratio of the first solvent-i: the first solvent-ii is 1:1.5), and monomer A' (2-acrylamide-2-methylpropanesulfonic acid), monomer B' (itaconic acid), monomer C' (N,N-dimethylacrylamide, and initiator G-1) are added to the first solvent-i and mixed evenly to obtain a mixed solution;

[0281] Wherein, the molar ratio of monomer A':monomer B':monomer C':initiator G-1:first solvent-i is 10:10:7:3:40;

[0282] (II) adding the first solvent-ii into a reactor, raising the temperature to 80° C., then uniformly dropping the mixed solution into the first solvent-ii at 80° C., the dropping process lasts for 4 hours, and then keeping the temperature for 4 hours to carry out polymerization reaction to obtain a reaction product system;

[0283] (III) The reaction product system is subjected to vacuum distillation to separate and remove methyl isobutyl ketone to obtain a polymer (denoted as D5).

[0284] In D5, the structural unit A in the hydrophilic main chain Structural unit B Structural unit C The molar ratio is 10:10:7; the structural unit D in the end-capping structure Structural unit E The molar ratio of D5 is 1:2.5; the weight average molecular weight of D5 is 47×10 4 g / mol.

[0285] Test Case

[0286] The polymers P1-P9 and D1-D5 prepared in Examples 1-9 and Comparative Examples 1-5 were respectively mixed with anhydrous ethanol and deionized water at a weight ratio of 10:1:30 to prepare oil well cement retarders (respectively denoted as S1-S9 and DS1-DS5);

[0287] The experimental oil well cement slurry was prepared using the above retarders S1-S9 and DS1-DS5. The cement slurry was prepared and the thickening time, water loss, free liquid and compressive strength of the cement slurry were tested in accordance with GB / T19139-2012 "Test Methods for Oil Well Cement".

[0288] Experimental oil well cement slurry formula: 100g Jiahua G-grade oil well cement + 25g microsilicon + 35g glass microspheres + 4g suspending agent BCJ-300S + 95g deionized water + 7.5g fluid loss reducer BXF-200L + 2.8g retarder + 2.5g drag reducer CF40L + 0.1g defoamer G603);

[0289] Among them, microsilicon: silicon content ≥95%, specific surface area 15-25m 2 / g;

[0290] Hollow glass microspheres: density 0.6g / cm 3 , diameter 5-30μm;

[0291] Suspension agent BCJ-300S: purchased from Tianjin PetroChina Boxing Engineering Technology Co., Ltd.;

[0292] Fluid loss reducer BXF-200L: purchased from Tianjin PetroChina Boxing Engineering Technology Co., Ltd.;

[0293] Drag reducer CF40L: purchased from Tianjin PetroChina Boxing Engineering Technology Co., Ltd.;

[0294] Defoaming agent G603: purchased from Tianjin PetroChina Boxing Engineering Technology Co., Ltd.

[0295] The results are shown in Table 1.

[0296] Table 1

[0297]

[0298] Note: In Table 1, the thickening temperature is 125°C, the test pressure is 90MPa, and the top temperature is 80°C.

[0299] As can be seen from Table 1, the oil well cement retarders S1-S9 prepared by using the polymers P1-P9 provided by the present invention have excellent retarding effect on the experimental oil well cement slurry, and the thickening time of the oil well cement slurry can reach more than 350 minutes, and the top compressive strength after 48 hours is greater than 7MPa ( Figure 2 is the thickening curve of the experimental cement slurry using retarder S1 at 125°C, with a thickening time of 432 min; Figure 3 This is the compressive strength development curve of the experimental cement slurry using retarder S1 at 80°C. It starts to harden and gain strength after 13.5 hours, and the compressive strength reaches 17.2MPa after 48 hours. The top strength develops quickly, and there is no super-retardation phenomenon. The water loss is not higher than 45mL, which meets the requirements of deep well cementing construction. Among them, retarders S1 and S2 show particularly excellent overall performance. The thickening time of oil well cement slurry reaches more than 430min, the top compressive strength reaches more than 12MPa after 48 hours, and the water loss is not higher than 40mL.

[0300] In addition, the ultra-long sealing section was simulated to return to the ground once, and the strength development of cement slurry was tested under the condition of top temperature of 30℃. Figure 4 This is the compressive strength development curve of the experimental cement slurry using retarder S1 at 30°C. The cement slurry begins to harden after 36 hours, and the compressive strength reaches 3.2 MPa after 48 hours. There is no super-retardation phenomenon, which can meet the requirements of cementing construction in long sealing sections.

[0301] The above effects show that the polymer and oil well cement retarder provided by the present invention can solve the problem of super-retarded setting of cement slurry at the top of a long sealing section in a deep well, the top strength develops quickly, has no effect on the water loss of cement slurry, has no free liquid, and has good engineering application prospects.

[0302] In particular, the retarder D1-D5 does not contain the polymer of the present invention, and cannot solve the problem of ultra-slow setting of cement slurry at the top of the long sealing section ( Figure 5 This is the thickening curve of the experimental cement slurry using the retarder DS1 at 125°C, with a thickening time of 406 min; Figure 6 This is the compressive strength development curve of the experimental cement slurry using retarder DS1 at 80°C. It has no strength at 48 hours, starts to harden at 130 hours, and maintains a low compressive strength. It has an ultra-retarded setting phenomenon and cannot meet the requirements of cementing construction in a long sealing section.

[0303] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polymer, characterized in that It includes a hydrophilic main chain and end-capping structures at both ends of the hydrophilic main chain; wherein, The hydrophilic main chain contains structural unit A, structural unit B and structural unit C; The structural unit A has a structure shown in formula (1); the structural unit B has a structure shown in formula (2); the structural unit C has a structure shown in formula (3); Wherein, R1, R2, R3, R4, and R5 are each independently selected from -H or C 1- C2 alkyl; R6 is selected from C1-C3 alkylene; Z is selected from H + , K + 、Na + or NH4 + ; R7, R8, R9, R 10 Each independently selected from -H, -CH3, -COOM 1 or -CH2COOM 2 , and R7, R8, R9, R 10 are not simultaneously selected from -H or -CH3; wherein M 1 、M 2 Each independently selected from H + , K + 、Na + or NH4 + ; R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from -H or C 1- C2 alkyl; The molar ratio of the structural unit A: structural unit B: structural unit C is 10: (0.5-8): (0.1-4); The end-capping structure has a structure shown in formula (4); Wherein, Q1, Q2 and Q3 are polymer segments, and Q1, Q2 and Q3 each independently contain a structural unit D and a structural unit E; wherein the structural unit D has a structure shown in formula (5); and the structural unit E has a structure shown in formula (6); Among them, R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 Each is independently selected from -H or -CH3; The molar ratio of the structural unit D:structural unit E is 1:(0.5-5).

2. The polymer according to claim 1, wherein R1, R2, R3, R4, R5 are each independently selected from -H or -CH3; R6 is -CH2-; R 11 , R 12 , R 13 , R 14 , R 15 are each independently selected from -H or -CH3; R 16 , R 17 , R 18 , R 19 , R 20 , R 21 and R 22 For -H, R 23 is -CH3; and / or, the molar ratio of the structural unit A: structural unit B: structural unit C is 10:(1-6):(1-3); And / or, the molar ratio of the structural unit D:structural unit E is 1:(1-3).

3. The polymer according to claim 1 or 2, wherein The weight average molecular weight of the polymer is (10-80)×10 4 g / mol.

4. A method for preparing a polymer, comprising: In the presence of a first solvent, monomer A', monomer B', monomer C' and initiator G are polymerized to obtain a polymer; Wherein, the monomer A' has a structure shown in formula (7); the monomer B' has a structure shown in formula (8); and the monomer C' has a structure shown in formula (9); Wherein, R1, R2, R3, R4, and R5 are each independently selected from -H or C 1- C2 alkyl; R6 is selected from C1-C3 alkylene; Z is selected from H + , K + 、Na + or NH4 + ; R7, R8, R9, R 10 Each independently selected from -H, -CH3, -COOM 1 or -CH2COOM 2 , and R7, R8, R9, R 10 are not simultaneously selected from -H or -CH3; wherein M 1 、M 2 Each independently selected from H + , K + 、Na + or NH4 + ; R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from -H or C 1- C2 alkyl; The initiator G has a structure shown in formula (10): Wherein, Q1, Q2, Q3, Q4, Q5, Q6 are polymer segments, and Q1, Q2, Q3, Q4, Q5, Q6 each independently contain a structural unit D and a structural unit E; wherein the structural unit D has a structure shown in formula (11); and the structural unit E has a structure shown in formula (12); Among them, R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 Each is independently selected from -H or -CH3; The molar ratio of the structural unit D: structural unit E is 1: (0.5-5); The molar ratio of the monomer A':monomer B':monomer C':initiator G is 10:(0.5-8):(0.1-4):(0.5-2).

5. The method according to claim 4, wherein: R1, R2, R3, R4, R5 are each independently selected from -H or -CH3; R6 is -CH2-; R 11 , R 12 , R 13 , R 14 , R 15 are each independently selected from -H or -CH3; R 16 , R 17 , R 18 , R 19 , R 20 , R 21 and R 22 For -H, R 23 is -CH3; and / or, the molar ratio of the structural unit D:structural unit E is 1:(1-3); And / or, the molar ratio of monomer A':monomer B':monomer C':initiator G is 10:(1-6):(1-3):(1-1.5).

6. The method according to claim 4 or 5, wherein: The first solvent is selected from alcohol solvents and / or ketone solvents; And / or, the polymerization reaction conditions include: temperature of 60-90° C. and time of 2-4 h.

7. The method according to claim 4 or 5, wherein: The preparation method of the initiator G comprises: (1) in the presence of a first catalyst, subjecting 5-bromo-1,2,3-pyrogallol to a first reaction with monomer D' and monomer E' to obtain a first product; Wherein, the monomer D' has a structure shown in formula (13); the monomer E' has a structure shown in formula (14); Among them, R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 Each is independently selected from -H or -CH3; (2) in the presence of a second solvent, subjecting the first product to a second reaction with metal powder L to obtain a second product; subjecting the second product to a third reaction with carbon dioxide to obtain a third product; and subjecting the third product to a fourth reaction in the presence of an acid, and separating the resulting product system to obtain a fourth product; (3) in the presence of a third solvent, subjecting the fourth product to a fifth reaction with thionyl chloride to obtain a fifth product; (4) subjecting the fifth product to a sixth reaction with hydrogen peroxide to obtain the initiator G.

8. The method according to claim 7, wherein: In step (1), the first catalyst is selected from at least one of boron trifluoride-ether complex, sodium hydroxide and potassium hydroxide; and / or, the molar ratio of 5-bromo-1,2,3-pyrogallol: first catalyst: monomer D': monomer E' is 1: (0.01-0.05): (1-3): (3-9); And / or, the conditions of the first reaction include: temperature of 100-150° C., pressure of 2.5-3 MPa, and time of 2-6 h.

9. The method according to claim 7, wherein: In step (2), the second solvent is an ether solvent; And / or, the gold powder L is selected from magnesium powder or zinc powder; and / or, the molar ratio of the first product: metal powder L: carbon dioxide is 1:(1-2):(2-4); And / or, the conditions of the second reaction include: temperature of -5-0°C, time of 3-5h; And / or, the conditions of the third reaction include: temperature of -5-0°C, time of 2-8h; And / or, the conditions of the fourth reaction include: temperature of 0-10°C, pH of 2-4, and time of 4-5h.

10. The method according to claim 7, wherein: In step (3), the third solvent is a benzene solvent; and / or, the molar ratio of the fourth product to thionyl chloride is 1:(5-7); And / or, the conditions of the fifth reaction include: temperature of 80-150° C. and time of 5-8 h.

11. The method according to claim 7, wherein: In step (4), the molar ratio of the fifth product to hydrogen peroxide is 1:(1.5-2); And / or, the conditions of the sixth reaction include: temperature of 30-40° C. and time of 2-4 h.

12. A polymer obtained by the preparation method according to any one of claims 4 to 11.

13. A retarder comprising: Host polymer and cosolvent; Wherein, the weight ratio of the main polymer:cosolvent is 10:(0.4-2); The main polymer is the polymer according to any one of claims 1 to 3 and 12.

14. The oil well cement retarder according to claim 13, wherein: The co-solvent is alcohol and / or ketone.

15. An oil well cement slurry comprising the retarder according to claim 13 or 14.

Citation Information

Patent Citations

  • Oxime ester compound and photoinitiator containing said compound

    CN103298782A

  • Process for preparing peroxide perfluoropolyethers

    CN1049670A

  • Adaptive-temperature high temperature retarder suitable for oil-gas well cementation, preparation method thereof and well cementing slurry

    CN109824823A

  • Polymerization initiator, polymer composition, method for free radical generation, lithographic printing plate material and method for manufacturing lithographic printing plate

    JP2004315594A